The notion of “killing”: causality, intention, and motivation in active and passive euthanasia - Fuchs, Thomas (Medicine, health care and philosophy, 1998)
As a new approach to the still unsettled problem of a morally significant difference between active and passive euthanasia, the meanings of the notion of killing are distinguished on the levels of causality, intention, and motivation. This distinction allows a thorough analysis and refutation of arguments for the equality of killing and letting die which are often put forward in the euthanasia debate. Moreover, an investigation into the structure of the physician's action on those three levels yields substantial differences between the two ways of acting. As can be demonstrated, only a teleological notion of the organism is able to grasp the characteristic feature of active euthanasia. On this basis it is argued that an action against the organism as a whole must, on the interpersonal level, be at once directed against the patient as a person himself.